Pembelajaran Tari Lenggang Patah pada Ekstrakurikuler Seni Tari di SMAN 1 Banyuasin 1: Penelitian - Teresa; Fery Firmasyah; Silo Siswanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine how the learning of the Lenggang Patah Sembilan dance is applied in extracurricular activities at SMAN 1 Banyuasin. The teacher provides dance training to students so that students can do it well. The learning materials or content used by the teacher for this dance extracurricular activity are in accordance with the work program that has been made. The teacher utilizes school facilities and infrastructure, such as laptops, projectors, and loudspeakers, so that all students can see and hear audio-visual learning materials. In accordance with the planned work program, each meeting is divided into three activities: introduction, core, and closing. In accordance with the planned work program, learning takes place for four meetings, with the researcher conducting an evaluative assessment at the last meeting. The components of the dance assessment derived from the wiraga, wirasa, and wirama aspects form an evaluative assessment. The results of the study, there were 68 wiraga assessments with an average score of 4.53, 66 wirama assessments with an average score of 4.40, and 58 wirasa assessments with an average score of 3.87. The average score was 85.33, and the total score was 1280. From the assessment results based on the dance assessment components, the overall average score of students ranged from 3.87 to 4.52.